Analysis of the educational policy management of the Chilean Ministry of Education based on teacher, student and leader perception surveys - Katherine López Arias (Universidad de La Rioja, 2014)
This research seeks to know the perceptions of integrating agents about the school management quality policies applied at a High School in the city ofPunta Arenas, Magellan and Antarctic Region. Thus, the Chilean educational policies and the concept of quality are dealt with. It is non-experimental, quantitative-qualitative descriptive study, approached from a mixed paradigm that analyzes this high school's management regarding the educational policies set forth by the Chilean Ministry of Education. For the quantitative approach a student and teacher survey is applied, whereas for the qualitative part an interview to the integrating agents (students, teachers, leaders and parents) is carried out. As a result, it is concluded that the ministry's educational policies are integrated in this high school's Institutional Development Plan. However, in practice, not all members of this educational community participate in the decision-making process, as its Strategic Plan does not take the interests of this educational community into account.